Critical Time Intervention: a qualitative study of the perspectives of prisoners and staff. Issue 1 (2nd January 2020) - Lennox, C.; Stevenson, C.; Edge, D.; Hopkins, G.; Thornicroft, G.; Susser, E.; Conover, S.; Herman, D.; Senior, J.; Shaw, J.
ABSTRACT: Release from prison is a vulnerable period, especially for people with severe mental illness. Critical Time Intervention (CTI) can be effective in improving service access and reducing negative outcomes. Nested within a randomised controlled trial of CTI, qualitative interviews were conducted with trial participants in both intervention (CTI) and treatment as usual (TAU) arms, CTI managers delivering the intervention and associated professionals. Data were analysed using a framework approach. Four themes were identified: uncertainty about post-release plans; inadequate housing provision; support during transition; and continuity of care. Interviewees shared common concerns about transition into the community but CTI participants felt less anxious about release and reported receiving more support with housing, access to services and community reintegration than during previous periods of incarceration. Professionals raised concerns about the time-limited nature of CTI and the impact of austerity measures on the availability of support following CTI. Implications for service delivery will be discussed.